MEF2C, a MADS/MEF2-family transcription factor expressed in a laminar distribution in cerebral cortex. - Leifer, D (1993)
We have cloned cDNA encoding a human transcription factor that belongs to the MEF2 (myocyte-specific enhancer-binding factor 2) subfamily of the MADS (MCM1-agamous-deficiens-serum response factor) gene family. This factor, which we have named MEF2C, binds specifically to the MEF2 element and activates transcription via this element. Specific isoforms of this factor are found exclusively in brain and are robustly expressed by neurons in cerebral cortex. In situ hybridization indicates that the factor is expressed preferentially in certain neuronal layers of cortex and that expression declines during postnatal development. The unusual pattern of expression in brain suggests that this transcription factor may be important in the development of cortical architecture.